Abdullah bin Abdul Kadir Munshi - Hadijah Rahmat 1958- (World Scientific, 2021)
"This book, Abdullah bin Abdul Kadir Munsyi: His Life, Voyages, and Legacies, is the most comprehensive, multi-disciplinary studies on Abdullah bin Abdul Kadir, widely known as Munsyi Abdullah (17961854). He was a prominent literary figure and thinker in the Malay world in the 19th century and was also an early 'pioneer' of Singapore. The author, Professor Hadijah Rahmat, has spent more than 25 years studying Munsyi Abdullah since her PhD studies in the School of Oriental and African Studies (SOAS), University of London, in 1992 to date. This book is covered in two volumes and is based on her research conducted using unexplored primary sources at several missionaries' archives at SOAS, London, Houghton Library, University Harvard, Library of Congress, Leiden University, KITVL, Holland, and the Perpustakaan Nasional Indonesia, Jakarta. The book consists of numerous academic papers presented at the regional and international seminars, and also published in international journals and as chapters of books. Besides academic papers, the excerpt of play titled Munsyi, sketches, poetry, and song, and interviews by the national media are also included. This book provides new insight into Abdullah's life, backgrounds, writings, his influences and legacies and the reactions and thought provoking views of the western and eastern scholars on Abdullah. The book is indeed the key reference for studies on Munsyi Abdullah, Malay literature, and the history of Singapore, Malaysia, and colonialism in Southeast Asia."